Mechanism of comparison in the structure of self-efficacy in junior athletes’ sporting activities - RAIEVSKA, YANA; SAVCHUK, OLEKSANDR; HULIAS, INESA; KHOKHLOV, ARTEM; HOIAN, IHOR; SYNIAKOVA, VIRA; SOROKA, OLENA; LUKASHOV, OLEKSANDR (My University, 2024)
This theoretical and empirical research examines the mechanism of comparison in the framework of self-efficacy in junior athletes’ sporting activities. The study included junior athletes of varying levels of qualification, participants in International, European, World, and Olympic sports competitions, aged 15 to 19 years. The sample parameters were as follows: n = 114; М = 17.91 years; SD = ±3.43; Me = 18.00. Methods. Valid methods widely used in sports psychology were employed to measure dependent variables such as comparison of capacities (CC) and comparison of opinions (CO), and independent variables including motivation for achieving success (MAS), motivation for avoiding failure (MAF), self-efficacy of subject activity (SSA), and self-efficacy of interpersonal communication (SIC). Statistically significant parameters were identified based on the comparison strategy. Results. A correlation matrix and a correlation pleiad of the investigated variables were created. We established seven statistically significant correlations of the parameters of comparison with independent variables (p≤.050; p≤.010) that testifies to a regular correlation of the psychological mechanism of comparison with the resultant parameters of educational-training, competitive and rehabilitative types of junior athletes’ sporting activities. It was found that the parameter “comparison of capacities” has a considerable impact on content subject activity that, in turn, can cause a probable danger. It was explained that critical ascending comparison of capacities can depress junior athletes and form wrong notions that a desirable result is unachievable since such comparisons have a direct impact on sporting subject activities. It was found that the parameter “comparison of opinions” is the most dependent parameter having a considerable impact on the quality of communication and motivational intentions to win. Discussion and conclusions. It was substantiated that the parameters of comparison of capacities and comparison of thoughts act as the psychological mechanism of impact on the resultant parameters of educational-training, competitive and rehabilitative areas of junior athletes’ sporting activities. Comparison can be a catalyst of juniors’ intentions of motivation and self-efficacy. Considering the obtained results in the educational-training process of sports schools for children and youth, junior academies of professional clubs, analytical departments of sports federations and coaching staffs can increase sports psychological literacy of the subjects of sporting activities and create a competitive advantage over rivals.
Keywords: motivation for achieving success; motivation for avoiding failure; mental health; competitiveness; self-regulation; self-actualization